NASIKH-MANSUKH PERSPEKTIF M. QURAISH SHIHAB DAN IMPLIKASINYA TERHADAP PENAFSIRAN - Fadil, Muhammad Reza; Basit, Abdul (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2025)
This article aims to analyze M. Quraish Shihab's views on the concept of nasikh-mansukh in the Quran and its implications for tafseer. The research was carried out using a literature review method on the works of M. Quraish Shihab related to the theme being studied. The results show that M. Quraish Shihab takes a compromise-reconciliatory attitude regarding two opinions that support and reject nasikh-mansukh in the Qur'an. It was carried out by reconstructing the meaning of nasikh-mansukh. For him, nasikh-mansukh does not mean erasing or canceling the law of the previous verse with the verse that follows, but changing the law according to the context without canceling the laws in each verse. This view has implications for his interpretation: first, all verses are still valid, or, in other words, no legal content in the Quran has been deleted; second, the discussion of the verses that Mansukh considered was moreless; Third, in the interpretation of the verse assessed by mansukh, the two opinions, both supporting and opposing, are explained without carrying out tarjih.